Serological survey for rabies in serum samples from vampire bats (desmodus rotundus) in botucatu region, SP, Brazil - Langoni, H. [UNESP]; Souza, L. C. [UNESP]; Zetun, C. B. [UNESP]; Silva TCC, [UNESP]; Hoffmann, J. L. [UNESP]; Silva, R. C. [UNESP] (FapUNIFESP (SciELO), 2008)
The chiropterans constitute 25% of the world's mammal fauna. Due to the destruction of their natural ecosystem, the vampire bats have moved from nature to artificial roosts closer to man and domestic animals. This phenomenon has happened particularly in rural areas. Rabies is a viral anthropozoonosis, 100% lethal, and vampire bats (Desmodus rotundus) represent an important role in its epidemiology. D. rotundus were captured at night with mesh nets in partnership with the Botucatu Defense Office and sent to the Zoonosis Diagnostic Service, at the School of Veterinary Medicine and Animal Husbandry, UNESP. Serum samples from 204 bats were analyzed by enzyme-linked immunosorbent assay (ELISA) and fluorescent antibody viral neutralization test (FAVN) for rabies antibody detection. The results showed 7.4% of sera with titers higher or equal to 0.5 U for rabies antibodies, which demonstrated viral flow circulation among the studied region. Data suggest a need for constant monitoring accomplished by epidemiological and sanitary measures.
Keywords: Desmodus rotundus; LPC-ELISA; Rabies virus; RFFIT; Vampire bats